Формування енергетичного суверенітету України: сучасний європейський та глобальний вимір - Ткач, Д.К. (Економіка промисловості, 2025)
Статтю присвячено аналізу сучасних підходів до формування енергетичного суверенітету України в контексті європейських і глобальних тенденцій. Розглянуто ключові чинники, що впливають на енергетичну незалежність країни, а саме: впровадження євроінтеграційних реформ, розвиток відновлюваних джерел енергії та зміцнення енергетичної безпеки. Особливу увагу приділено викликам воєнного часу та перспективам подальшої інтеграції України в європейський енергетичний простір. Підкреслено важливість стратегічного планування для забезпечення стабільного та сталого розвитку енергетичного сектору країни. The problem of forming Ukraine’s energy sovereignty is not only a technical or economic task, but also a key element of national security, geopolitical resilience, and post-war recovery. For decades, the country’s energy sector was characterized by significant dependence on fossil fuel imports and high energy intensity, which made it vulnerable to external pressure. This vulnerability became especially evident after the full-scale invasion, accompanied by systematic missile strikes on critical infrastructure. Despite its destructive nature, this crisis has created a unique window of opportunity for a fundamental transformation of the energy system. Purpose of the study. The aim of the research is a comprehensive analysis of the institutional and economic foundations for building a new architecture of Ukraine’s energy security in the conditions of post-crisis transformation, as well as an assessment of its European and global dimension. Methods. The study uses the analytical method to assess damages based on data from the KSE Institute and other open sources. A systemic approach was applied to structure information on physical damage, economic losses, and humanitarian consequences. The method of comparative analysis was also used to study recovery strategies and integration with the European market. Results. It was determined that as of 2024–2025, Ukraine has lost, damaged, or has occupied more than 60% of its generating capacity. Nevertheless, thanks to colossal recovery efforts and the implementation of physical protection, the energy system has demonstrated high resilience. The key strategic direction has been the decentralization of the energy system, which involves a shift to less vulnerable, distributed sources of generation. An important aspect is integration with the European market, confirmed by physical synchronization with ENTSO-E in March 2022 and the adoption in July 2025 of a draft law that creates the legal basis for market integration with the EU. At the same time, Ukraine’s post-war recovery is taking place against the background of global energy transformations and the European Green Deal, which creates synergy for decarbonization and reducing dependence on fossil fuels. Perspectives. The long-term strategy envisions a complete rejection of the centralized model and a transition to a “green” transformation. The implementation of this strategy is crucial for strengthening Ukraine’s energy security and economic recovery, ensuring its integration into the global energy space.